Decarbonizing heat in the European buildings sector: options, progress and challenges - Bassam Fattouh; Anouk Honoré (Oxford Energy Forum: A Quarterly Journal for Debating Energy Issues and Policies, 2023)
This edition of the Oxford Energy Forum is dedicated to the challenges posed by the decarbonization of heat in the European buildings sector. Decarbonization of energy systems has become a key topic as both the EU and individual countries, including the UK, attempt to achieve carbon neutrality by 2050. So far, the electricity sector has been the main focus of low-carbon policies, but if the region is to meet its long-term environmental target, efforts will need to expand to other sectors, including the heating sector, which is the region's largest single energy user, covering about 50 per cent of its final energy demand. Although the heating sector is moving towards low-carbon energy, almost half of the energy used in the residential sector still comes from the direct combustion of fossil fuels (natural gas, oil, and even some coal). In 2021, more than 35 per cent came from natural gas alone. Record high gas prices over the past 18 months have increased the focus on how we heat our homes, adding affordability and energy security concerns to the environmental benefits of decarbonizing the housing fleet. The energy transition in the European buildings sector relies on two main pillars: lowering the energy demand and decarbonizing the energy supply. Reducing the energy needed to keep buildings warm can be done by improving the insulation and energy performance of existing buildings, supported by behavioural changes by consumers to increase energy conservation. Given the complexity of scaling up deep energy-efficiency retrofits and the significant proportion of old buildings in Europe, it is imperative to look for solutions to decarbonize the heat supply. Alternatives to fossil fuel sources for heating buildings are available (heat pumps, district heating, or even decarbonized gases), but there is no silver bullet and options need to be adapted to local needs and circumstances. One of the key conclusions of this issue is that the decarbonization of buildings will need to have a central role in the transition to a zero-carbon future, but the task is enormous and lacks implementation speed. Much needs to be done, and some of it will take time. The 15 articles in this edition of the Oxford Energy Forum discuss some of the key aspects of the puzzle: the existing building stock, the pace and extent of renovation, and the existing low-carbon options with a focus on heat pumps and district heating, highlighting their main benefits but also the key challenges facing their deployment, the policies implemented and their shortcomings, the problems linked to inadequate taxation, the importance of local diversities, and the issue of energy poverty. Specific cases are used to illustrate these various questions.
Keywords: 330